Diffusion tensor imaging of sport related concussion in adolescents. Issue 5 (11th March 2013) - Virji-Babul, Naznin; Borich, Michael; Makan, Nadia; Moore, Tiffany; Frew, Kira; Emery, Carolyn A; Boyd, Lara
Abstract : Objectives: To establish the short-term changes in white matter integrity following sport related concussion in adolescents and to examine the association between changes in white matter integrity and a clinical measure of concussion. Design: Cross-sectional within cohort study. Setting: University hospital and community ice hockey arenas. Subjects: Twelve adolescents with sport related concussion (ages 14–17 years) within 2 months of injury and 10, active adolescents with no previous history of concussion. Assessment of Risk Factors: Adolescents within 2 months of sport-related concussion and healthy adolescents with no history of concussion were assessed using the Sport Concussion Assessment Tool 2 (SCAT2) and total SCAT2 score (/100) was considered. Outcome Measures: Two measures of diffusion tensor imaging (DTI): fractional anisotropy (FA) and mean diffusivity (MD). Results: Whole brain FA values were significantly increased (F (1, 40)=6.29, p=0.01) and MD values decreased (F(1, 40)=4.75, p=0.036) in concussed athletes compared with control participants. SCAT2 total scores were associated with whole brain FA and MD values with lower scores associated with higher FA (R 2 =0.25, p=0.017) and lower MD (R 2 =0.2, p=0.038). Conclusion: This preliminary study provides evidence of microstructural changes in the integrity of the white matter in adolescent athletes following a sport related concussion. In addition, we found a relationship between measures of white matter integrity and the SCAT2 up to 16–61 days following concussion, which may indicate persistent structural change in the adolescent brain after injury. Further study should chart the trajectory of brain injury and recovery in this population. Acknowledgements: Martha Piper Research Fund, University of British Columbia and the Brain Research Centre, University of British Columbia. Competing interests: None.